Variation in the pattern of circle of willis in human brain - A morphological study and review - Iman Sinha; Asis Kumar Ghosal; Ratul Basu; Indra Dutta (Al Ameen Medical College, 2014)
Background: Variation of "Circulus Arteriosus" is frequent. Knowledge of the variations of vascular anatomy of Circle of Willis will guide the neurosurgeons during intracranial surgery. Objectives: This is an analytical study, where the aim of our study is to analyze the variations regarding shape, symmetry, length and diameters of the component arteries. The study also includes other variations like absence, duplication and abnormal origin of component arteries. Methods: In the present study 80 specimens of human brains of both sexes, aged between 20-60 years are obtained from voluntary body donation at the Department of Anatomy and fresh corpses undergoing autopsy at the Department of Forensic and State Medicine in a teaching hospital in Kolkata. Careful observation & measurement of the component arteries are done after proper preservation and necessary dissection. The findings are then recorded and analyzed. Results: 62 out of total 80 specimens (77.5%) have been found to be complete, symmetrical and having normal length and caliber. 7 specimens (6.25%) were incomplete and not heptagonal in shape. Conclusion: Out of 22.5% variations most of the variations are seen in posterior communicating artery (10%), followed by anterior cerebral artery (6.25%) and anterior communicating artery (6.25%). Most common type of variation is hypoplasia.